The Effect of Problem Solving Learning Models to Improve Learning Outcomes of History - Ima, Wa; Sopacua*, Jems (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Learning is essentially a process of interaction between students and their environment, resulting in a change in behavior for the better. The results of observations made at Nusalaut Central Maluku Christian High School in history subjects, it is known that the cognitive learning outcomes of students are still low. One learning model that can train students in overcoming these problems is to apply the problem solving model. This study aims to improve history learning outcomes through a problem solving model in class XI students for the 2022/2023 academic year. The subjects of this class action research were 30 students in class XI as the recipients of the action, while the subjects of the action were the history teacher as the teacher, colleagues as the subjects observing the learning process, and the school principal as the data source subject. Methods of data collection are done through test techniques, observation and documentation. This action research was conducted in two cycles, each cycle consisting of planning, action, observation and reflection. The results of this study indicate that the use of problem solving learning models can improve the history learning outcomes of class XI SMA Kristen Nusalaut. This can be seen from the average value of student history learning outcomes which also increased, namely before the action of 70.93 in the first cycle of 77.85 and in the second cycle of 85.46. In addition, the percentage of student learning completeness, namely before the action was 66.67%, in cycle I was 73.33% and in cycle II was 93.33%.